2010
DOI: 10.4194/trjfas.2010.0103
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The acute toxicity of ammonium sulphate, calcium ammonium nitrate and two different composite fertilizers [15:15:15 (NPK-1) and 25:5:10 (NPK-2)] to juvenile rainbow trout (Oncorhynchus mykiss; 0.89±0.22 g) was evaluated under semistatic conditions. The concentrations of ammonium sulphate, calcium ammonium nitrate, NPK-1 and NPK-2 that killed 50% of the rainbow trout within 96-h (96-h LC 50 ) were 0.149, 0.259, 0.258 and 0.408 g/L, respectively. The mortality of fish was elevated with increasing concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…in African catfish with the decrease in Hb, Hct and RBCs. Capkin et al [34] reported decrease in Hct content of dogfish, Scyhorhinus canicula after 24-hr exposure to Cd. They attributed this decrease in Hct content to hemodilution.…”
Section: Physiological Changesmentioning
confidence: 99%
“…in African catfish with the decrease in Hb, Hct and RBCs. Capkin et al [34] reported decrease in Hct content of dogfish, Scyhorhinus canicula after 24-hr exposure to Cd. They attributed this decrease in Hct content to hemodilution.…”
Section: Physiological Changesmentioning
confidence: 99%
“…Ammonia is the main ingredient of fertilizer exists in two interchangeable forms in water, i.e. unionized ammonia (more toxic) and ammonia ions (less toxic) and their ratio can be controlled by pH and temperature [27]. Heavy metals and other dissolved contaminants have been identified by EPA 2000 [28] as primary toxicant, i.e.…”
Section: Chemical Fertilizer Industrial Effluentsmentioning
confidence: 99%